Lithium batteries and other electrochemical storage systems - Glaize, Christian (ISTE., 2013)
Lithium batteries were introduced relatively recently in comparison to lead- or nickel-based batteries, which have been around for over 100 years. Nevertheless, in the space of 20 years, they have acquired a considerable market share - particularly for the supply of mobile devices. We are still a long way from exhausting the possibilities that they offer. Numerous projects will undoubtedly further improve their performances in the years to come. For large-scale storage systems, other types of batteries are also worthy of consideration: hot batteries and redox flow systems, for example.